Beyond the Corporate Lens: The Use of Humor in Activist Communication - Wolf, Katharina (Peter Lang Publishing Inc., 2014)
Less structured types of activism, such as community groups and social movements, are prevalent in society, but have been largely ignored in scholarly PR research to date. This article highlights humour as a communications tool in grassroots activism, thereby adding to the discipline’s understanding of diversity in professional communication. Largely underutilised within a corporate context, humorous actions may promptly be dismissed as immature, unprofessional behaviour, assuming a lack of seriousness and communications expertise. However, the paper argues that humour performs a vital role in activist communication, particularly for those groups that are traditionally labelled too insignificant to be recognised by corporate stakeholder mapping exercises. Drawing on intensive periods of participant observation within one of Australia’s most prominent social movements, this paper identifies four core functions of humour in activist communication, which aid activists in conveying their key messages, but also ensure consistency and the long term survival of the group.